Pengujian Formulasi Ekstrak Praxelis clematidea dan Buah Lerak terhadap Pertumbuhan Gulma Rottboellia exaltata - Pujisiswanto, Hidayat; Sriyani, Nanik; Susanto, Herry (J-Plantasimbiosa, 2025)
The presence of Rottboellia exaltata weeds is one of the factors causing crop failure in agricultural land such as corn cultivation. Praxelis clematidea weeds and lerak fruit were found to have allelopathic effects in suppressing the growth of many plants. This study aims to determine the effect of P. clematidea and lerak fruit extract formulations on the germination and growth of R. exaltata weeds. The study was conducted from July to October 2025 in Bandar Lampung City and the Weed Science Laboratory, Faculty of Agriculture, University of Lampung. The study used a completely randomized block design (CRBD) with 5 replications. The treatments consisted of 5 formulations of P. clematidea and lerak fruit extracts, namely P0 = control (without extract); P1 = 50% P. clematidea extract; P2 = 50% lerak fruit extract; P3 = 25% P. clematidea extract + 75% lerak fruit extract; P4 = 50% P. clematidea extract + 50% lerak fruit extract; P5 = 75% P. clematidea extract + 25% lerak fruit extract. The results showed that post-emergence application of a mixture of P. clematidea extract + lerak fruit extract inhibited weed growth. The inhibitory effect of 75% P. clematidea extract + 25% lerak fruit extract was higher than that of other formulations on weed height, number of leaves, dry weight of shoots, dry weight of roots, and total dry weight of weeds. The low crown/root ratio, weed toxicity level of 78.67%, and the highest weed suppression percentage of R. exaltata at 67.64%.